On Models of Commercial Fishing: The Traditional Literature Needs No Defenders - Smith, Vernon L. (Journal of Political Economy, 1972)
Examines the models of commercial fishing. Representation of the variable K as a measure of crowding externality in the cost function; Change of the degree of fishing pressure without changing the variable K; Modification of the output of firms by varying the inputs.